A Review of Traditional Project Procurement Towards Integrated Practice - Mohd Nawi, Mohd Nasrun; Abdul Nifa, Faizatul Akmar; Ahmed, Vian (AENSI, 2014)
As a new integrated procurement approach, Integrated Project Delivery (IPD) has been introduced as an alternative towards improving sustainability and integrated construction performance. Currently, however, most of the project procurement or method in Malaysia are still based on the traditional construction process approach; fragmented and separation of the design and construction phase. This traditional construction process has been widely criticized for its fragmented approach to project delivery and its failure to form effective teams. Due to that problem, a number of issues have recently arisen in current construction methods, such as reworks, time delay, rising costs, lack of communication and coordination, and wastages. This paper through literature review aims to explore this fragmentation issue especially in the design and build (DB) and clarify how far it affects the process of project delivery. Suggestion on how an integrated project delivery (IPD) approach for design and construction process in order to minimise the fragmentation issue will be concluded.